The effect of celebrity endorsement effectiveness on consumers' attitude towards advertisement and purchase intention - Siti Nazihah, Mohd Jamili (2015)
This study attempts to study the association between the consumers’ attitude towards advertisement and the intention to purchase the product that being advertisement. The variable is the celebrity endorsement variables namely attractiveness, trustworthiness and expertise of the model in the print advertisement. These variables is later was after tested on its association with the independent variable which is the attitude towards advertisement. A questionnaire was developed from previous similar study. The questionnaire was later pilot tested. A total of 200 questionnaires were distributed to the public in the Territory of Putrajaya. 158 completed questionnaires were returned. Both the descriptive and inferential statistical analysis was conducted on the data collected. The study found that all variable in the study has an association between the variables. Finally, attitude towards advertisement has an effect of R2 0.338 on the intention to purchase